Prostor kot konstitutivni element kanadske imaginacije in njenih retoričnih ubeseditev - Potocco, Marcello (Primerjalna književnost, 2013)
The article is a case study analyzing space as part of the Canadian national myth. Following a short study of two typical renderings of the relation between space and its rhetoric counterparts (in the poetry of John Newlove and E. J. Pratt), the author offers a critical overview of the Canadian imaginary of space as predominantly constituted in the works of E. J. Pratt, Northrop Frye, and Margaret Atwood, as well as an overview of their poststructuralist detractors.
Keywords: literatura in prostor; kanadska književnost; nacionalna mitologija; kulturna identiteta; kulturni imaginarij; severna meja